In vitro activity ofN-benzenesulfonylbenzotriazole on Trypanosoma cruzi epimastigote and trypomastigote forms - Becerra, María Cecilia (2012)
Chagas disease is still an important health problem in Central and South America. However, the only drugs currently available for specific treatment of this disease may induce toxic side effects in the host. The aim of this work was to determine the activity of N-benzenesulfonylbenzotriazole (BSBZT) against the protozoan parasite Trypanosoma cruzi. The effects of BSBZT and benzotriazole (BZT) were compared to those of benznidazole (BZL) on epimastigote and trypomastigote forms. BSBZT was found to have an in vitro growth inhibitory dose-dependent activity against epimastigotes, with flow cytometry analysis confirming that the treated parasites presented size reduction. BSBZT showed an IC50 of 21.56 μg/mL (81.07 μM) against epimastigotes at 72 h of incubation, whereas BZT did not affect the growth of this parasite form. Furthermore, the toxic effect of BSBZT, was stronger and appeared earlier (at 24 h) in trypomastigotes than in epimastigotes, with the LC50 of this compound being 28.40 μg/mL (106.79 μM) against trypomastigotes. The concentrations of BSBZT used in this study presented low hemolytic activity and cytotoxicity. Consequently, at concentrations near IC50 and LC50 (25 μg/mL), BSBZT caused only 2.4% hemolysis and 15% of RAW 264.7 cell cytotoxicity. These results reveal the potential of BSBZT as a prototype in drug design for developing new anti-T. cruzi compounds.